Effect of metformin on serum vitamin B12 and red blood cell indices in North Indian subjects with diabetes mellitus - Husain, Amir; Khan, Haroon Subhan; Siddiqi, Sheelu Shafiq; Mukherjee, Amit (International Journal of Advances in Medicine, 2022)
Background: Diabetes mellitus (DM) affecting almost half a billion people worldwide and India is amongst the top ten countries of adults with diabetes. Metformin, the first-line therapy for diabetes, is associated with vitamin B12 malabsorption and subsequently, the development of vitamin B12 deficiency/insufficiency could manifest severe complications like neuropathy or anemia in the future. This study evaluated the effect of metformin on vitamin B12 and RBC indices in the North Indian population. Methods:This study was executed at a tertiary care hospital. 35 T2DM (type 2 DM) participants with ongoing metformin therapy were compared with 27 T2DM participants without metformin therapy. Participants were recruited from outpatient after diagnosis as per American diabetes association (ADA) criteria. Results: Metformin-treated participants had significantly low hemoglobin (t=2.096, df=60, 0.0403) compared to untreated participants. Similarly, MCHC was significantly lower in the metformin group (mean=33.28 gm/dl) compared to non-metformin group (mean=34.53 gm/dl) (t=2.745, df=60, p=0.0080). Moreover, there was a strong negative correlation (r=-0.4613, p=0.0053) among vitamin B12 and MCV in metformin group. There was no statistically significant correlation between vitamin B12 and RBC indices (MCV, MCH, MCHC) in the non-metformin group. Analyzing contingency table (Fisher’s exact test), we found no major difference (p=0.2002) between two groups of vitamin B12 with an odds ratio of 2.026 (95% CI=0.7366 to 5.633). Unpaired t test also confirmed insignificancy (t=0.04077, df=60, p=0.9676). Conclusions:Strong negative correlation was observed between vitamin B12 and MCV. Despite the insignificant difference of vitamin B12 between metformin and non-metformin groups, significantly low MCHC was found in metformin-treated participants.